Brazilian ground pearl damaging blackberry, raspberry and blueberry in Brazil - Efrom,Caio Fábio Stoffel (2012)
The Brazilian ground pearl, Eurhizococcus brasiliensis (Wille, 1922) (Hemiptera: Margarodidae), is a subterranean, polyphagous scale insect native of Southern Brazil that feeds on a variety of different vineyard plant species (Vitis spp.). In this study, it is reported three new plant hosts of the species. In 2007 and 2010, infested plants were documented in the towns of Farroupilha (29°14'34"S, 51°23'20"W) and Vacaria (28°26'30"S, 50°52'59"W) in Rio Grande do Sul, Brazil. Specimens of the ground pearl were found in the roots of three cultivated berry plants: blackberry (Rubus spp.), raspberry (Rubus idaeus L.) and blueberry (Vaccinium sp.). Observed symptoms included: chlorotic leaves, gradual wasting, reduced production, and mortality. Given the increasing popularity of berry orchards in the region, this study serves as an alert for farmers to avoid establishing them in areas infested with the ground pearl and to check for the insects in the root cuttings used to establish berry crops.